2021
DOI: 10.1088/1755-1315/924/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fermentation time and grain concentration for water kefir production from butterfly pea flower (Clitoria ternatea)

Abstract: Herbal tea is known rich in bioactive compounds and pigments. Herbal tea can be derived from Butterfly pea flowers. Butterfly pea has a high level of anthocyanins and flavonoid levels. However, butterfly pea has not been used optimally in fermentation products such as water kefir. Water kefir has many benefits and potential antioxidant sources. This research aimed to optimize fermentation time (24-48 hours) and concentration grain (5-15%) for the production of butterfly pea water kefir with a good antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is a natural pigment in plants, imparting several colors, namely, blue, red, and purple, to flowers, fruits, and leaves. Due to its natural colorant, C. ternatea flower extract has been used in previous studies as food colorant as well as to improve the functionality of the products [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is a natural pigment in plants, imparting several colors, namely, blue, red, and purple, to flowers, fruits, and leaves. Due to its natural colorant, C. ternatea flower extract has been used in previous studies as food colorant as well as to improve the functionality of the products [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Research has explored using various raw materials, including rosella flower tea, butterfly pea flower, soursop leaf tea, and kersen leaves. These studies have reported increased flavonoid content, anthocyanins, antioxidant activity, and the production of volatile organic compounds (VOCs), all contributing to enhanced functionality in water kefir [62][63][64][65][66][67].…”
Section: The Potential Development Of Cbs As a Fermented Functional B...mentioning
confidence: 99%
“…The use of milk-or water-kefir grains (MKG and WKG) have been used as starters for the fermentation processes of substrates such as milk [27,28], and whey [12], herbal teas [29], vegetable juices [30], and fruit juices [31,32]. Numerous reports indicate the health benefits of beverages fermented with these granules [17,26,[33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%